The broad host range pathogen Pseudomonas aeruginosa strain PA14 carries two pathogenicity islands harboring plant and animal virulence genes - He, Jianxin (National Academy of Sciences, 2004)
The ubiquitous bacterium Pseudomonas aeruginosa is the quintessential opportunistic pathogen. Certain isolates infect a broad range of host organisms, from plants to humans. The pathogenic promiscuity of particular variants may reflect an increased virulence gene repertoire beyond the core P. aeruginosa genome. We have identified and characterized two P. aeruginosa pathogenicity islands (PAPI-1 and PAPI-2) in the genome of PA14, a highly virulent clinical isolate. The 108-kb PAPI-1 and 11-kb PAPI-2, which are absent from the less virulent reference strain PAO1, exhibit highly modular structures, revealing their complex derivations from a wide array of bacterial species and mobile elements. Most of the genes within these islands that are homologous to known genes occur in other human and plant bacterial pathogens. For example, PAPI-1 carries a complete gene cluster predicted to encode a type IV group B pilus, a well known adhesin absent from strain PAO1. However, >80% of the PAPI-1 DNA sequence is unique, and 75 of its 115 predicted ORF products are unrelated to any known proteins or functional domains. Significantly, many PAPI-1 ORFs also occur in several P. aeruginosa cystic fibrosis isolates. Twenty-three PAPI ORFs were mutated, and 19 were found to be necessary for full plant or animal virulence, with 11 required for both. The large set of “extra” virulence functions encoded by both PAPIs may contribute to the increased promiscuity of highly virulent P. aeruginosa strains, by directing additional pathogenic functions.